Neu eröffnete musikalische Bibliothek - Mizler, Lorenz Christoph 1711-1778; Friederike Luise von Preußen 1714-1784 (Hilversum Knuf, 1966)
Lorenz Mizler took his degree in music in 1736 at the University of Leipzig, where he lectured on music history ('Die gelehrte Historie der Musik'), mathematics, and philosophy. Aiming to “confer on music the shape of a science," Mizler lay at the basis of the development of 'Musikwissenschaft'. He was closely connected to Christian Wolff and Johann Mattheson.
The 'Vorrede' to part one is dated 20 October 1736. Vol. II contains elements from Uffenbach's 'Gesammelte Neben-Arbeit' (see 10J16)
Vol. 1 was originally published in 1736-39, vol. 2 in 1740-43, vol. 3 in 1746-52, and vol. 4 in 1754.
Lorenz Mizlers Der Weltweisheit und der freyen Künste Lehrers auf der Academie zu Leipzig / und der Societet der musikalischen Wissenschafften Miglieds und Secretarius Neu eröffnete Musikalische Bibliothek Oder Gründliche Nachricht nebst unpartheyischem Urtheil von musikalischen Schriften und Büchern. Erster Band Welcher bestehet aus sechs Theilen, nebst den darzu gehörigen Kupfern und Registern / Zweyter Band, Welcher bestehet aus vier Theilen, nebst den darzu gehörigen XXXVI. Kupfertafeln und Registern
Keywords: Aristoxenos -- 360/354 BC-c. 300 BC; Meibom, Johann Heinrich -- 1590-1655; Gibelius, Otto -- 1612-1682; Wallis, John -- 1616-1703; Printz, Wolfgang Caspar -- 1641-1717; Quirsfeld, Johann -- 1642-1686; Werckmeister, Andreas -- 1645-1706; Beer, Johann -- 1655-1700; Fux, Johann Joseph -- 1660-1741; Kellner, David -- 1670-1748; Muratori, Ludovico Antonio -- 1672-1750; Mattheson, Johann -- 1681-1764; Telemann, Georg Philipp -- 1681-1767; Bach, Johann Sebastian -- 1685-1750; Gottsched, Johann Christoph -- 1700-1766; Karl-Marx-Universität (Leipzig, Germany); 18th Century (1701-1800); Periodical; Music criticism; Poetry; Composing; Basso continuo; Method; Keyboard instrument; Temperament; Solmization; Opera; Leipzig (Germany)